Faktor penentu kepuasan wisatawan dalam mengikuti program cooking class pada restoran di ubud bali - Adi, Kadek Suara; Ariani, Ni Made; Aryanti, Ni Nyoman Sri (Jurnal Kepariwisataan dan Hospitalitas, 2017)
This research the back ground this of the price and promotion competition against the restaurant that has cooking class program in Ubud, than resulting in a decrease the number of tourist who following cooking class program. The aims of this research is to know determinants factor of tourist satisfaction following cooking class program at restaurant in Ubud, Bali. Data that obtained in this research come from observation, interviews, questioner, and review from literature. Technique determination of sample used is quota sampling with 75 respondent number of sample. Data analysis technique used is statistic descriptive, likert scale, statistic inferential, validation test, reliability test with SPSS 17.0 and factor analysis. Based The determinant factor of tourist satisfaction following cooking class program consist wist reliability, responsiveness, assurance, empathy, tangible, with each variable has 3 indicators such as: instructor, material, and method. The total factors are 15 factors.  Based the value of Masure of Sampling Asequancy (MSA) is more than 0.5.so it can be continue for factor analysis hence there is no factor wasted. Based on factor analysis obtained six factors which influence tourist satisfaction following cooking class program at restaurant in Ubud Bali with loading factor value 60,407%. First factor is Instructor Skill with value 2,453, second factor is Contents of Material with value 1,771, Third factor is Instructor with value 1,480, Fourth factor is Teaching Methods with value 1,245, Fifth factor is Material with value 1,092 and the sixth factor is Empathy of Instructor with value 1,020. From the six factor, the dominant factor which determinant tourist satisfaction following cooking class program at restaurant in Ubud Bali is Instructor Skill with  eigenvalue 2,453 and has percent of variance value 16.354%. Based the result of this research, the suggestion that propose for owner of restaurant who has cooking class program should more attend the empathy of instructor because with give a sense of empathy that is expected by tourist can attract tourist interest following cooking class program. This research the back ground this of the price and promotion competition against the restaurant that has cooking class program in Ubud, than resulting in a decrease the number of tourist who following cooking class program. The aims of this research is to know determinants factor of tourist satisfaction following cooking class program at restaurant in Ubud, Bali. Data that obtained in this research come from observation, interviews, questioner, and review from literature. Technique determination of sample used is quota sampling with 75 respondent number of sample. Data analysis technique used is statistic descriptive, likert scale, statistic inferential, validation test, reliability test with SPSS 17.0 and factor analysis. Based The determinant factor of tourist satisfaction following cooking class program consist wist reliability, responsiveness, assurance, empathy, tangible, with each variable has 3 indicators such as: instructor, material, and method. The total factors are 15 factors.  Based the value of Masure of Sampling Asequancy (MSA) is more than 0.5.so it can be continue for factor analysis hence there is no factor wasted. Based on factor analysis obtained six factors which influence tourist satisfaction following cooking class program at restaurant in Ubud Bali with loading factor value 60,407%. First factor is Instructor Skill with value 2,453, second factor is Contents of Material with value 1,771, Third factor is Instructor with value 1,480, Fourth factor is Teaching Methods with value 1,245, Fifth factor is Material with value 1,092 and the sixth factor is Empathy of Instructor with value 1,020. From the six factor, the dominant factor which determinant tourist satisfaction following cooking class program at restaurant in Ubud Bali is Instructor Skill with  eigenvalue 2,453 and has percent of variance value 16.354%. Based the result of this research, the suggestion that propose for owner of restaurant who has cooking class program should more attend the empathy of instructor because with give a sense of empathy that is expected by tourist can attract tourist interest following cooking class program. This research the back ground this of the price and promotion competition against the restaurant that has cooking class program in Ubud, than resulting in a decrease the number of tourist who following cooking class program. The aims of this research is to know determinants factor of tourist satisfaction following cooking class program at restaurant in Ubud, Bali. Data that obtained in this research come from observation, interviews, questioner, and review from literature. Technique determination of sample used is quota sampling with 75 respondent number of sample. Data analysis technique used is statistic descriptive, likert scale, statistic inferential, validation test, reliability test with SPSS 17.0 and factor analysis. Based The determinant factor of tourist satisfaction following cooking class program consist wist reliability, responsiveness, assurance, empathy, tangible, with each variable has 3 indicators such as: instructor, material, and method. The total factors are 15 factors.  Based the value of Masure of Sampling Asequancy (MSA) is more than 0.5.so it can be continue for factor analysis hence there is no factor wasted. Based on factor analysis obtained six factors which influence tourist satisfaction following cooking class program at restaurant in Ubud Bali with loading factor value 60,407%. First factor is Instructor Skill with value 2,453, second factor is Contents of Material with value 1,771, Third factor is Instructor with value 1,480, Fourth factor is Teaching Methods with value 1,245, Fifth factor is Material with value 1,092 and the sixth factor is Empathy of Instructor with value 1,020. From the six factor, the dominant factor which determinant tourist satisfaction following cooking class program at restaurant in Ubud Bali is Instructor Skill with  eigenvalue 2,453 and has percent of variance value 16.354%. Based the result of this research, the suggestion that propose for owner of restaurant who has cooking class program should more attend the empathy of instructor because with give a sense of empathy that is expected by tourist can attract tourist interest following cooking class program.